2014
DOI: 10.1128/mbio.00936-13
|View full text |Cite
|
Sign up to set email alerts
|

Models Derived fromIn VitroAnalyses of Spleen, Liver, and Lung Leukocyte Functions Predict Vaccine Efficacy against the Francisella tularensis Live Vaccine Strain (LVS)

Abstract: Currently, there are no licensed vaccines and no correlates of protection against Francisella tularensis, which causes tularemia. We recently demonstrated that measuring in vitro control of intramacrophage bacterial growth by murine F. tularensis-immune splenocytes, as well as transcriptional analyses, discriminated Francisella vaccines of different efficacies. Further, we identified potential correlates of protection against systemic challenge. Here, we extended this approach by studying leukocytes derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 43 publications
7
55
0
Order By: Relevance
“…The mediators identified included cytokines and other mediators known to play mechanistic roles, such as gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) (13,14), and those that were subsequently found to play critical roles, such as interleukin-6 (IL-6) (17) and IL-12 receptor ␤2 (IL-12r␤2) (18), thus validating the approach. In addition, when the quantification of multiple selected markers was combined in multivariate analyses, the resulting models were significantly correlated with survival (19). However, our studies also found that the expression of potential correlates of protection varied slightly among mouse strains (12), routes of injection (19), and, importantly, the tissue sources of immune cells (19).…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…The mediators identified included cytokines and other mediators known to play mechanistic roles, such as gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) (13,14), and those that were subsequently found to play critical roles, such as interleukin-6 (IL-6) (17) and IL-12 receptor ␤2 (IL-12r␤2) (18), thus validating the approach. In addition, when the quantification of multiple selected markers was combined in multivariate analyses, the resulting models were significantly correlated with survival (19). However, our studies also found that the expression of potential correlates of protection varied slightly among mouse strains (12), routes of injection (19), and, importantly, the tissue sources of immune cells (19).…”
mentioning
confidence: 61%
“…In addition, when the quantification of multiple selected markers was combined in multivariate analyses, the resulting models were significantly correlated with survival (19). However, our studies also found that the expression of potential correlates of protection varied slightly among mouse strains (12), routes of injection (19), and, importantly, the tissue sources of immune cells (19).…”
mentioning
confidence: 61%
See 3 more Smart Citations